Teletherapy Matters – Mental health and materialities of care in domestic more-than-digital assemblages - Kolehmainen, Marjo; Lupton, Deborah (Elsevier BV, 2026)
Teletherapy involves the coming together of humans and nonhuman agents to accomplish a therapeutic encounter. This article presents novel insights into the ways in which the absence or presence of different creatures, spaces and objects, both digital and non-digital, contribute to psychological therapies at a distance. Building on contributions from more-than-human theory, science and technology studies (STS) and the sociology of health, we identify these beings and things as active and co-constitutive of therapeutic care. Empirically, our analysis draws on in-depth interviews with 39 Finnish therapy and counselling professionals conducted after the onset of the COVID-19 pandemic, when they turned from in-office appointments to teletherapy during periods of stay-at-home and social distancing public health orders. The professionals conducted remote therapy from their own homes while their clients engaged with them from their own domestic settings. Findings show that in particular, these professionals saw the home setting (both their own and that of their clients) as an important component in these heterogeneous more-than-digital assemblages of care. In some cases, therapeutic capacities were opened by these assemblages. However in other situations, opportunities for professionals to provide support were closed by the distractions and affective atmospheres of the domestic settings in which both professionals and their clients were attempting to enact a successful therapeutic encounter.